OPTIMALISASI RADIUS SERVER SEBAGAI SISTEM OTENTIKASI DAN OTORISASI UNTUK PROSES LOGIN MULTI APLIKASI MIKHMON MENGGUNAKAN USER MANAGER DI MIKROTIK - Sabar Hanadwi putra (Sekolah Tinggi Teknik - PLN, 2018)
ABSTRACT The development and application of science and technology has a very important impact on various aspects of activities which include wireless communication. In daily life various security measures can be carried out through communication devices used by managers, when managing users as a step to integrate several different applications can be done by optimizing the server radius as the authentication and authorization stages for multi-application login process called mikhmon. this is to implement an authentication and authorization system for the multi-application mikhmond login process by optimizing the use of the radius server. The results of this study indicate that in testing the radius server optimization process as an authentication system and this authorization can make users only have one single account for several different applications and a time base voucher results show that the user cannot log in again when the voucher time is up. Keywords: Mikrotik, Mikhmon, Usermanager, Otentikasi,Otorisasi.